PEMBELAJARAN LARI JARAK PENDEK MENGGUNAKAN PENDEKATAN PERMAINAN LARI BOLA KERANJANG (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2013)
This research represent research of class action which consist of two cycle where each;everycycle consist of 4 phase that is planning, action, observation ( and pengamatan) of refleksi.Technique data collecting in this research use assessment of perception of attitude livelinesof student, complete assessment [of] result learn, and also enquette of respon / student comments.Result of perception of study process which [is] its bearing with student activity attitudeduring following study, that is cycle of I result of percentage of equal to 72,00% andcycle of II result of percentage of equal to 92,00%, this there [is] make-up of equal to 20,00%.While is complete [of] result learn student [pass/through] result of this research show theexistence of the make-up of that is cycle of I tired 72,72 % and cycle of II tired 90,91%, thisthere [is] make-up of equal to 18,19%. And result of enquette analysis of respon student getrespon which are positive from student. This seen from student mean 80,91% student answervery agree / very interesting / very like to follow study. This can be said that [by] studenttake a fancy to presented study model. Conclusion in this research [is] study run short-hauluse approach of game run basket ball can improve result learn student. While suggestion inthis research [is] student expected to increase the spirit [of] learning. Teacher shall continueout for improve its ability as well as teacher expected more inovatif, creative in chosening andapplying method and also study media matching with Iesson items, so that school activity canwalk pleasant and effective